Evaluasi Penggunaan Moda Transportasi Bus Trans Metro Deli Rute Lapangan Merdeka – Pinang Baris Di Kota Medan - Hermansyah Hermansyah; Amsuardiman Amsuardiman; Muammar Nawawi (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2022)
Transportation has a very significant role in various aspects such as social, economic, environmental, and others. Therefore, the problems faced by almost all big cities in Indonesia are congestion, air pollution and traffic congestion. This mode of transportation consists of land, water and air transportation modes. For the land transportation mode itself, it is subdivided into road and rail modes. Public Transportation is passenger transportation using public transportation and is carried out with a Rent or Pay system. This study is to measure the level of passenger service with the Customer Saticfaction Index method. With the aim of knowing how much interest the people of Medan are in using the Trans Metro Deli Corridor of Pinang Baris Terminal – Medan Merdeka Square. the calculation of the questionnaire data was carried out using the Customer Saticfaction Index (CSI) method to calculate the service quality of Trans Metro Deli Medan, that the level of service obtained was satisfactory with a passenger satisfaction level of 73%. The factors that do not satisfy passengers are in terms of the condition of the bus stop and service information